Greater than recommended stiffness and power setting of a stance-phase powered leg prosthesis can improve step-to-step transition work and effective foot length ratio during walking in people with transtibial amputation - Tacca, Joshua R.; Colvin, Zane A.; Grabowski, Alena M. (Frontiers in Bioengineering and Biotechnology, 2024)
People with unilateral transtibial amputation (TTA) using a passive-elastic prosthesis exhibit lower positive affected leg trailing work (ALtrail Wpos) and a greater magnitude of negative unaffected leg leading work (ULlead Wneg) during walking than non-amputees, which may increase joint pain and osteoarthritis risk in the unaffected leg. People with TTA using a stance-phase powered prosthesis (e.g., BiOM, Ottobock, Duderstadt, Germany) walk with increased ALtrail Wpos and potentially decreased magnitude of ULlead Wneg compared to a passive-elastic prosthesis. The BiOM includes a passive-elastic prosthesis with a manufacturer-recommended stiffness category and can be tuned to different power settings, which may change ALtrail Wpos, ULlead Wneg, and the prosthesis effective foot length ratio (EFLR). Thirteen people with TTA walked using 16 different prosthetic stiffness category and power settings on a level treadmill at 0.75–1.75 m/s. We constructed linear mixed effects models to determine the effects of stiffness category and power settings on ALtrail Wpos, ULlead Wneg, and EFLR and hypothesized that decreased stiffness and increased power would increase ALtrail Wpos, not change and decrease ULlead Wneg magnitude, and decrease and not change prosthesis EFLR, respectively. We found there was no significant effect of stiffness category on ALtrail Wpos but increased stiffness reduced ULlead Wneg magnitude, perhaps due to a 0.02 increase in prosthesis EFLR compared to the least stiff category. Furthermore, we found that use of the BiOM with 10% and 20% greater than recommended power increased ALtrail Wpos and decreased ULlead Wneg magnitude at 0.75–1.00 m/s. However, prosthetic power setting depended on walking speed so that use of the BiOM increased ULlead Wneg magnitude at 1.50–1.75 m/s compared to a passive-elastic prosthesis. Ultimately, our results suggest that at 0.75–1.00 m/s, prosthetists should utilize the BiOM attached to a passive-elastic prosthesis with an increased stiffness category and power settings up to 20% greater than recommended based on biological ankle values. This prosthetic configuration can allow people with unilateral transtibial amputation to increase ALtrail Wpos and minimize ULlead Wneg magnitude, which could reduce joint pain and osteoarthritis risk in the unaffected leg and potentially lower the metabolic cost of walking.